PENGUATAN MANAJEMAN UMKM BERBASIS MOBILE PADA USAHA KEBAB - Berliana Siregar; Diajeng Mulyani; Parameswari, Nazma (Universitas Haji Sumatera Utara, 2025)
ABSTRACT enhancement of Micro, Small, and Medium Enterprises (MSMEs) management through technology-based assistance for the